Emerging Traditional and Pharmacological Health Benefits of Trachyspermum ammi (Ajwain): Future Aspects - Agarwal, Uma; Pannu, Arzoo; Tonk, Rajiv Kumar (Current Functional Foods, 2026)
Trachyspermum ammi, commonly known as Ajwain or Carom seeds, is a versatile medicinal plant of the Apiaceae family, widely utilized in traditional medicine systems, including Ayurveda, Unani, and Siddha. This review consolidates the phytochemical composition, traditional applications, and pharmacological activities of T. ammi alongside its potential in modern therapeutics. A systematic methodology was employed to gather data, focusing on peer-reviewed articles, ethnobotanical reports, and experimental studies published in renowned databases. Specific search terms such as “Trachyspermum ammi,” “Ajwain pharmacology,” and “phytochemical analysis” were used to extract relevant information. Selection criteria included recent advancements in phytochemistry, pharmacology, and therapeutic applications, ensuring a comprehensive synthesis of traditional knowledge and modern scientific evidence. Ajwain seeds, characterized by their bioactive components such as thymol and carvacrol, exhibit a broad spectrum of pharmacological properties, including antioxidant, anti-inflammatory, antimicrobial, antihypertensive, and antidiabetic effects. Emerging evidence highlights its role in combating neurodegenerative diseases, cancer, and metabolic disorders. Despite its established uses, further studies on the pharmacokinetics, bioavailability, and clinical efficacy are essential. Advanced drug delivery systems, such as nanoencapsulation and lipid-based formulations, are discussed as strategies to enhance the stability and bioavailability of Ajwain's active compounds. This review emphasizes integrating traditional knowledge with modern scientific approaches to unlock Ajwain’s full therapeutic potential, addressing existing limitations and paving the way for its incorporation into evidence-based healthcare practices. Future directions include comprehensive clinical trials, standardization of extracts, and exploration of its role in gut microbiota modulation and integrative medicine.
Keywords: carom seeds